Baseline information on prokaryotic and microeukaryotic plankton communities inside and outside of Indonesian marine lakes - Cleary, D. F. R. (2020)
Marine lakes represent a unique and globally rare aquatic environment characterised by lower salinities and pH and higher temperatures than the surrounding open water environment. Here we provide baseline data on planktonic communities of Archaea, Bacteria and microeukaryotes inside and outside (open water habitat) of three marine lakes (Kakaban, Haji Buang and Tanah Bamban) in the Berau region of Indonesia. Compositional variation was highly congruent with the major axis of variation separating open water from marine lake samples for all three domains. Planktonic Archaea mainly consisted of OTUs assigned to Euryarchaeota that were closely related to organisms in Genbank previously obtained from seawater samples. The majority of archaeal OTUs were most abundant in open water habitat with a few OTUs abundant in all habitats. Most bacterial sequences were assigned to Proteobacteria, Cyanobacteria and Bacteroidetes with the percentage of Cyanobacteria highest in two of the marine lakes and lowest in the remaining lake (Tanah Bamban). In contrast to Archaea, there were a number of bacterial OTUs that were markedly more abundant in marine lake habitat. Most microeukaryote sequences were assigned to the Alveolata, Stramenopiles, Opisthokonta, Archaeplastida and Hacrobia. As was the case with Bacteria, a number of abundant microeukaryote OTUs were more abundant in marine lake habitat. Our results thus indicate similar compositional responses to the environmental conditions in marine lake habitat across the major domains of life and point to marine lakes harbouring distinct microbial communities.